The product manager's toolkit : methodologies, processes, and tasks in technology product management - Steinhardt, Gabriel (Springer, 2017)
This book provides a consistent and holistic managerial approach to product management and presents a practical and comprehensive methodology (roles, processes, tasks, and deliverables) that covers all aspects of product management. It helps students of product management, product management practitioners, product management organizations, and corporations understand the value, theory, and implementation of product management. It outlines a practical approach to clarify role definitions, identify responsibilities, define processes and deliverables, and improve the ability to communicate with stakeholders. The book details the fundamentals of the Blackblot Product Manager's Toolkit® (PMTK) product management methodology, a globally adopted best practice.
Keywords: Product management.; New products -- Management.; High technology industries -- Marketing.; elektronické knihy; electronic books